Bilingual children weigh speaker’s referential cues and word-learning heuristics differently in different language contexts when interpreting a speaker’s intent - Hung, Wan-Yu; Patrycia, Ferninda; Yow, W. Q. (Frontiers in Psychology, 2015)
Past research has investigated how children use different sources of information such as social cues and word-learning heuristics to infer referential intents. The present research explored how children weigh and use some of these cues to make referential inferences. Specifically, we examined how switching between languages known (familiar) or unknown (unfamiliar) to a child would influence his or her choice of cue to interpret a novel label in a challenging disambiguation task, where a pointing cue was pitted against the mutual exclusivity (ME) principle. Forty-eight 3-and 4-year-old English-Mandarin bilingual children listened to a story told either in English only (No-Switch), English and Mandarin (Familiar-Switch), English and Japanese (Unfamiliar-Switch), or English and English-sounding nonsense sentences (Nonsense-Switch). They were then asked to select an object (from a pair of familiar and novel objects) after hearing a novel label paired with the speaker’s point at the familiar object, e.g., “Can you give me the blicket?” Results showed that children in the Familiar-Switch condition were more willing to relax ME to follow the speaker’s point to pick the familiar object than those in the Unfamiliar-Switch condition, who were more likely to pick the novel object. No significant differences were found between the other conditions. Further analyses revealed that children in the Unfamiliar-Switch condition looked at the speaker longer than children in the other conditions when the switch happened. Our findings suggest that children weigh speakers’ referential cues and word-learning heuristics differently in different language contexts while taking into account their communicative history with the speaker. There are important implications for general education and other learning efforts, such as designing learning games so that the history of credibility with the user is maintained and how learning may be best scaffolded in a helpful and trusting environment.